Updated data on Psilocybe (Hymenogastraceae, Agaricales) from the southern Brazil region and a newly proposed species - Silva, Paula Santos Da; Ramírez-Cruz, Virginia; Bradshaw, Alexander James; Dentinger, Bryn T.m.; Guzmán-Dávalos, Laura; Villalobos-Arámbula, Alma Rosa; Silveira, Rosa Mara Borges Da (Phytotaxa, 2026)
Psilocybe is a well-known genus of fungi, commonly referred to as “magic mushrooms”, due to its production of psychoactive compounds. Research interest in this genus has experienced a resurgence due to its relevance as a potential therapy for a growing global mental health crisis. In this study, 62 specimens representing 10 species of Psilocybe from southern Brazil were examined using morphological data and rDNA ITS sequences in some of them. Here, we report new records of P. subaeruginascens and P. yungensis, providing new information about the occurrence and range of these species. In addition, a novel species from southern Brazil, Psilocybe araucariicola, is characterized and introduced using morphological characteristics and DNA sequencing. Phylogenetic analyses using rDNA ITS, rpb2, and tef1 sequences were performed to determine the relationship of P. araucariicola to other species within Psilocybe. Morphological description, illustrations, photographs, and phylogenetic analysis results of P. araucariicola are provided.